A Prospective Cohort Study on Quality of Life among the Pediatric Population after Surgery for Recurrent Patellar Dislocation - Alexandru Herdea; Vlad Pencea; Claudiu N. Lungu; Adham Charkaoui; Alexandru Ulici (Children, 2021)
Patellofemoral instability is a frequent cause of knee pathology affecting quality of life among the pediatric population. Here, we present a prospective cohort study which included patients who had undergone surgical management using the lateral release and medial imbrication approach (LRMI) or medial patellofemoral ligament reconstruction (MPFL-R). The object of this study was to assess the quality of life among children that have undergone surgical treatment for patellar dislocation. Quality of life was assessed before and after surgery using the Pediatric International Knee Documentation Committee form (Pedi-IKDC), a questionnaire that aims to quantify knee functionality. Postoperative scarring was evaluated using The Stony Brook Scar Evaluation Scale. One hundred and eight patients were selected and grouped according to the type of procedure. Before surgery, the two groups had similar mean Pedi-IKDC scores (41,4 MPFL-R vs. 39,4 LRMI p = 0.314). Improvements were observed in the postoperative scores. The MPFL-R technique showed promising outcomes. When comparing the two surgical groups, there was a significant difference in favor of MPFL-R group (MPFL-R 77.71 points vs. LRMI 59.74 points, p < 0.0001–95% CI (11.22–24.72)). Using the Stony Brook Scar Evaluation Scale, a significant difference in scar quality in favor of MPFL-R was observed (4,5 MPFL-R vs. 2,77 LRMI p = 0.002). In conclusion, this study provides objective evidence-based outcome assessments that support the medial patellofemoral ligament reconstruction technique as the gold standard for patellofemoral instability.